C4F: USM AND APUCEN ASSIST NEPAL EARTHQUAKE VICTIMS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
KATHMANDU, NEPAL, August 2015 Universiti Sains Malaysia (USM) has widened its involvement in the universitycommunity engagement programme at the global level by providing assistance to victims of the earthquake, measuring 7.8 on the Richter scale, which devastated Nepal on 25 April through the ‘Coaching4Fun Against the Quakes’ (C4F) pioneer project.